Scalable SOCP-based localization technique for wireless sensor network - Randa M. Abdelmoneem; Eman Shaaban (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2016)
Node localization is one of the essential requirements to most applications of wireless sensor networks. Thispaper presents a detailed implementation of a centralized localization technique for WSNs based on SecondOrder Cone Programming (SOCP). To allow scalability, it also proposes a clustered localization approachfor WSNs based on that centralized SOCP technique. The cluster solves the SOCP problem as a globalminimization problem to get positions of the cluster sensor nodes. To enhance localization accuracy, a clusterlevel refinement step is implemented using Gauss-Newton optimization. The initial position for the Gauss-Newton optimization is the position drawn from the preprocessor SOCP localization. The proposed approachscales well for large networks and provides a considerable reduction in computation time while yielding goodlocalization accuracy.